Simulation of fluid flow and mass diffusion in irradiator tube - Chowdhury, Showkat Jahan (Journal of Mechanical Engineering, 2008)
This paper presents a numerical study of fluid flow and mass transfer in an irradiator tube. Optical fibers and wires are drawn through a coating die to apply protective coating of synthetic materials, and then passed through a glass tube where UV light from the surrounding irradiators causes curing of the coating materials. During this curing process, fumes are generated which needs to be washed out of the tube before it diffuses to the glass wall and causes tube smoking, a problem faced in the industries. Calculations are done to study the effect of laminar and turbulent flow, flow rate and tube diameter. Numerical simulation for the purging air flow and mass transfer of the generated chemical species is done using a computational model and results are presented. The irradiator tube flow with a lip at exit, as normally used by the industry is first simulated. The mass concentration profiles show that the concentration of generated species near the glass tube wall is high, which explains tube smoking. Simulations are repeated without the lip, and the mass concentration near the tube wall is found to be much less, which suggests elimination of tube smoking problem. Computations are also done for larger tube diameter and without the lip, which gives lowest mass concentration near the glass wall. Experiments are carried out to verify the simulated results. Experimental results show that irradiator tube smoking occurs for lip condition, but by removing the lip the tube smoking problem can be eliminated, which is desirable. DOI: 10.3329/jme.v38i0.894 Journal of Mechanical Engineering Vol.38 Dec. 2007 pp.8-13